Exotic tree species have consistently lower herbivore load in a cross‐ A tlantic tree biodiversity experiment - Sylvie Berthelot; Jürgen Bauhus; Carsten F. Dormann; Dominique Gravel; Christian Messier; Charles A. Nock; Alain Paquette; Peter B. Reich; Jochen Fründ (Ecology, 2023)
It is commonly expected that exotic plants experience reduced herbivory, but experimental evidence for such enemy release is still controversial. One reason for conflicting results might be that community context has rarely been accounted for, although the surrounding plant diversity may moderate enemy release. Here, we tested the effects of focal tree origin and surrounding tree diversity on herbivore abundance and leaf damage in a cross‐Atlantic tree‐diversity experiment in Canada and Germany. We evaluated six European tree species paired with six North American congeners in both their native and exotic range, expecting lower herbivory for the exotic tree species in each pair at each site. Such reciprocal experiments have long been called for, but have not been realized thus far. In addition to a thorough evaluation of overall enemy release effects, we tested whether enemy release effects changed with the surrounding tree diversity. Herbivore abundance was indeed consistently lower on exotics across all six tree genera (12 comparisons). This effect of exotic status was independent of the continent, phylogenetic relatedness, and surrounding tree diversity. In contrast, leaf damage associated with generalist leaf chewers was consistently higher on North American tree species. Interestingly, several species of European weevils were the most abundant leaf chewers on both continents and the dominant herbivores at the Canadian site. Thus, most observed leaf damage is likely to reflect the effect of generalist herbivores that feed heavily on plant species with which they have not evolved. At the German site, sap suckers were the dominant herbivores and showed a pattern consistent with enemy release. Taken together, the consistently lower herbivory on exotics on both continents is not purely a pattern of enemy release in the strictest sense, but to some degree additionally reflects the susceptibility of native plants to invasive herbivores. In conclusion, our cross‐Atlantic study is consistent with the idea that nonnative trees have generally reduced herbivory, regardless of tree community diversity and species identity, but for different reasons depending on the dominant herbivore guild.

A geospatial modeling approach to quantifying the risk of exposure to environmental chemical mixtures via a common molecular target - Kristin M. Eccles; Agnes L. Karmaus; Nicole C. Kleinstreuer; Fred Parham; Cynthia V. Rider; John F. Wambaugh; Kyle P. Messier (Science of The Total Environment, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Arm?trunk coordination in the absence of proprioception - E. Tunik; H. Poizner; M. F. Levin; S. V. Adamovich; J. Messier; Y. Lamarre; A. G. Feldman (Experimental Brain Research, 2003)

Genetic structure of the world’s polar bear populations - D. Paetkau; S. C. Amstrup; E. W. Born; W. Calvert; A. E. Derocher; G. W. Garner; F. Messier; I. Stirling; M. K. Taylor; Ø. Wiig; C. Strobeck (Molecular Ecology, 1999)
We studied genetic structure in polar bear ( Ursus maritimus ) populations by typing a sample of 473 individuals spanning the species distribution at 16 highly variable microsatellite loci. No genetic discontinuities were found that would be consistent with evolutionarily significant periods of isolation between groups. Direct comparison of movement data and genetic data from the Canadian Arctic revealed a highly significant correlation. Genetic data generally supported existing population (management unit) designations, although there were two cases where genetic data failed to differentiate between pairs of populations previously resolved by movement data. A sharp contrast was found between the minimal genetic structure observed among populations surrounding the polar basin and the presence of several marked genetic discontinuities in the Canadian Arctic. The discontinuities in the Canadian Arctic caused the appearance of four genetic clusters of polar bear populations. These clusters vary in total estimated population size from 100 to over 10 000, and the smallest may merit a relatively conservative management strategy in consideration of its apparent isolation. We suggest that the observed pattern of genetic discontinuities has developed in response to differences in the seasonal distribution and pattern of sea ice habitat and the effects of these differences on the distribution and abundance of seals.

Determinants of Home Range Size for Polar Bears ( Ursus maritimus ) - S.H. Ferguson; M.K. Taylor; E.W. Born; A. Rosing‐Asvid; F. Messier (Ecology Letters, 1999)
The mean home range size of female polar bears ( Ursus maritimus ; 125 100 km 2 ± 11 800; n = 93) is substantially larger than the predicted value (514 km 2 ) for a terrestrial carnivore of similar weight. To understand this difference, we correlated home range size and sea ice characteristics. Home range size was related to (i) the ratio of land vs. sea within a given home range (42% of explained variance), and (ii) seasonal variation in ice cover (24%). Thus, bears using land during the ice‐free season had larger home ranges and bears living in areas of great seasonal variation in ice cover also had larger home ranges. In another analysis we investigated how variation in a bear’s environment in space and time affects its choice of home range. We found that polar bears adjusted the size of their home range according to the amount of annual and seasonal variation within the centre of their home range. For example, polar bears experiencing unpredictable seasonal and annual ice tended to increase their home range size if increasing home range size resulted in reducing variation in seasonal and annual ice. Polar bears make trade‐offs between alternate space‐use strategies. Large home ranges occur when variable ice cover is associated with more seals but also a more unpredictable distribution of those seals.

Comparison of variability of initial kinematics and endpoints of reaching movements - Julie Messier; J. F. Kalaska (Experimental Brain Research, 1999)